Terapinė jurisprudencija – kelias pasitikėjimo teise link. Mediacijos atvejis - Grybauskaitė, Dominyka; Jakaitytė, Ugnė (Vilnius University Open Series, 2024)
The article analyses the implementation of therapeutic jurisprudence in mediation. Therapeutic jurisprudence is an interdisciplinary field of study that seeks to explore how the negative effects of legislation and the application of law can be reduced and the therapeutic effects enhanced. The judicial process often exacerbates an existing conflict and intensifies the negative experiences caused by the conflict itself. Therefore, the objectives of therapeutic jurisprudence can be achieved through alternative dispute resolution methods, including mediation. The work reveals how aims and principles of mediation implement the ideas of therapeutic jurisprudence and how the use of mediation allows for the achievement of a socially beneficial goal of increasing trust in the legal system. The article provides a comparative analysis of mediation in family cases in Canada and Lithuania and assesses whether the ideas of therapeutic jurisprudence are implemented in Lithuania through the institute of family dispute mediation. The comparative analysis of Lithuanian and Norwegian regulation of mediation in criminal justice shows that that the Norwegian model of victim-offender mediation can serve as a model for the realization of the goals of therapeutic jurisprudence in Lithuania.